Characterization of Dynamic Slug Flow Induced Loads in Pipelines - Reda, Ahmed; Forbes, Gareth; Sultan, I. (ASME, 2012)
The flow of a liquid mass, i.e. a ‘slug’, inside thin-walled spanning pipelines, produces a lateral traversing force. This moving force initiates dynamic stresses within the structure and is often critical when assessing structural fatigue. Moving slugs in spanning pipelines may be modeled as either a moving concentrated force or a moving mass when investigating the vibration response of the pipeline under the passage of a slug flow. The moving concentrated force model only yields accurate results when the mass of the slug is small in relation to that of the pipeline; although, the moving mass model should be used instead when the slug‘s mass cannot be regarded as small in relation to the mass of the pipeline. The modeling of a moving concentrated force is much more readily implemented than that of a moving mass. Thus, the aim of this paper is to identify those situations where the simplification of considering a moving concentrated force can be made, or indeed if dynamic analysis is even required. Results are given in this paper to quantify when the two modeling techniques begin to differ significantly. It is intended that this paper will assist pipeline engineers discriminate between which appropriate conditions to use for either of the two different models of a traversing concentrated force/mass over a structure.